Use of oral health care services by family caregivers and care recipients: the LENTO intervention - Shanza Razzaq; Irma Nykänen; Tarja Välimäki; Sohvi Koponen; Roosa-Maria Savela; Ursula Schwab; Anna Liisa Suominen (Medical Journals Sweden, 2024)
Objective: We aimed to evaluate the impact of an individually tailored preventive oral health intervention on the use of oral health care services by older family caregivers (FCs) and their care recipients (CRs). Material and methods: A randomized controlled six and 12-month oral health intervention study included FCs and CRs aged ≥65 years living in Eastern Finland. The participants were randomly assigned to an intervention (FCs n = 53, CRs n = 47) and a control (FCs n = 39, CRs n = 35) group. Individually tailored oral health interventions for the FCs provided by a dental hygienist focused on oral hygiene and self-care. Generalized estimating equations were used to analyze the impact of intervention on the change in the use of oral health care services. Results: The intervention had no significant effect on the use of oral health care services by the FCs or their CRs. Traditional factors such as female gender, a higher number of teeth, toothache, no dental fear, and higher morbidity were significantly (p < 0.05) associated with an increased use of oral health care services in the FCs, but not among the CRs. Conclusions: Individually tailored preventive oral health intervention showed no effect on the use of oral health care services. To promote oral health among the elderly, specific interventions focusing on use of oral health care services are needed. Trial registration: clinicaltrials.gov/study/NCT04003493